Efek Antihiperurikemia Ekstrak Air Kelopak Bunga Rosela (Hibiscus sabdariffa L.) pada Tikus Putih Wistar Jantan - Wahyuningsih, Sri; Yulinah, Ellin; Sukrasno, .; N, Karina (Jurnal Farmasi Sains dan Terapan, 2015)
Antihyperuricemia effectivity had been studying of water extract roselle calyx (Hibiscus sabdariffa L.) in Wistar male rats used at 46.25 mg/kgBW, 92.5 mg/kgBW and 185 mg/kgBW by using uricostatic methods. In uricostatic method had used drug comparison alopurinol 9 mg/kgBW of an induced with potassium oxonate 250 mg/kgBW peritoneally and high purin diet which contained 10% seed of Gnetum gnemon administrations within 14 days. The test of uric acid content had observed on day 1, 7 and 14. The results showed in uricostatic method with alopurinol as drug comparison that water extract of roselle calyx at doses 46,25 mg/kgBW and 185 mg/ kgBW had capability decreased the level of uric acid (p